1969
DOI: 10.1115/1.3591683
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the One-Dimensional Equilibrium Cutting Gap in Electrochemical Machining

Abstract: In electrochemical machining the evolution of gas and heat in the electrolyte results in local variation of the gap between the electrodes. The ability to predict these variations for any given operating condition is a prerequisite of proper design of the cathode tool. This paper provides analytical predictions of the change in gap geometry for the one-dimensional steady-state case. Employing the basic conservation laws, a system of coupled nonlinear differential equations is derived for the gas-electrolyte mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…by the electrochemical machining method requires correct design of the tool cathode (Hopenfeld and Cole, 1969). Gusseff first filed a patent on electrochemical machining (ECM) in 1929 and found that ECM is suitable for high-strength and high-melting point alloys (1988).…”
Section: Introductionmentioning
confidence: 99%
“…by the electrochemical machining method requires correct design of the tool cathode (Hopenfeld and Cole, 1969). Gusseff first filed a patent on electrochemical machining (ECM) in 1929 and found that ECM is suitable for high-strength and high-melting point alloys (1988).…”
Section: Introductionmentioning
confidence: 99%
“…The ECM process is the coupling function of electrochemistry, the electric field and the liquid field. Either void fraction or temperature of the electrolyte is taken into account in the majority of the papers [7][8][9] (Clark and McGeough, 1977;Kawafune et al, 1967;Hopenfeld and Cole, 1969). Chang and Hourng [10-11] (1999, 2001) proposed a onedimensional or two-dimensional, two-phase fluid flow model and showed that most ECM can be treated as a quasi-steady process.…”
Section: Introductionmentioning
confidence: 99%
“…Plastic or press dies, wiredrawing dies, optical and electric parts are good examples [10]. The experimental results of Mileham et al showed that the quality of the machined surface would be influenced by the current density, flow rate of electrolyte and the gap width [11]. ECM uses sufficient current density for the removal of an electrically conductive metal by anodic dissolution when the anode and cathode are separated by a narrow gap containing an electrolyte flowing at high-pressure [12].…”
Section: Introductionmentioning
confidence: 99%